Effects of Gold Mine Tailings as an Additive on the Tribological Performance of Lubricating Polyurea Grease - Xiaodong Liu; Heping Wang; Rongshe Wang; Binglong Zhang; Jiqing Wang; Wei Wang; Xihong He (Lubricants)
Lubricating greases with varying proportions of gold mine tailings or SiO2 as additives were prepared, and their friction and wear performance were evaluated using a four-ball tribometer. Scanning electron microscopy and three-dimensional surface profilometry were employed to analyze the thickener properties and wear patterns on the steel balls. The results indicated that the addition of gold mine tailings significantly improved the friction-reducing and wear-resistant properties of the base grease compared with SiO2. At the optimal concentration of 3 wt%, the addition of gold mine tailings reduced the coefficient of friction and wear scar diameter of the base grease by 43.2% and 21.1%, respectively, yielding the best performance among the 11 tested samples. Further analysis revealed that silicate and calcium carbonate particles in the gold mine tailings were deposited on the surface, forming a protective layer. This layer, along with the grease film, contributed to substantial reductions in both friction and wear.